Effects of nutrients and warming on Planktothrix dynamics and diversity: a palaeolimnological view based on sedimentary DNA and RNA. (29th September 2014) - Savichtcheva, Olga; Debroas, Didier; Perga, Marie Elodie; Arnaud, Fabien; Villar, Clément; Lyautey, Emilie; Kirkham, Amy; Chardon, Cécile; Alric, Benjamin; Domaizon, Isabelle
Summary Decennial changes in Planktothrix rubescens diversity and dynamics were reconstructed by applying molecular tools to analyse DNA and RNA extracted from lake sediments. The sediments studied were sampled from a deep peri‐alpine lake that has experienced both dramatic shifts in trophic conditions and large‐scale climatic changes. Palaeolimnological proxies were combined with statistical modelling to investigate the relative influence of phosphorus concentrations and temperature changes on the extent of Planktothrix blooms over the last century. Phylogenetic analysis revealed that the overall composition of the cyanobacterial community changed over the transition from oligotrophic to eutrophic conditions. When the relative abundance of Planktothrix decreased in the 1970s, concomitant with eutrophication, total cyanobacterial abundance remained high and more Anabaena and Microcystis sequences were detected. In spite of such drastic environmental changes, the lake provided a constant niche for one particular Planktothrix species, which was consistently present from the 1920s to the present day. Phosphorus concentration was found to be the dominant driver of the relative abundance of P. rubescens, with the highest abundances observed during mesotrophic conditions. The relative role of climate was nutrient‐dependent, with warmer springs having a positive effect on P. rubescens abundance only during mesotrophic periods. Overall, this study confirms that analysis of genetic signatures preserved in sediment archives allows assessment of key palaeoenvironmental indicator species that have no diagnostic microscopic cellular features in the sediment record. In the case of cyanobacteria, palaeogenetics offer unique opportunities to anticipate how future climate change might affect the response of P. rubescens to phosphorus concentration.